2001
DOI: 10.1054/bjoc.2000.1632
|View full text |Cite
|
Sign up to set email alerts
|

Expression of individual lamins in basal cell carcinomas of the skin

Abstract: In this study we used a unique collection of type specific anti-lamin antibodies to study lamin expression patterns in normal human skin and in skin derived from patients with basal cell carcinomas (BCCs). Lamin expression in serial sections from frozen tissue samples was investigated by single and double indirect immunofluorescence. In normal skin, lamin A was expressed in dermal fibroblasts and in suprabasal epithelial cells but was absent from all basal epithelial cells. Lamin C was expressed in dermal fibr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
87
2

Year Published

2005
2005
2015
2015

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 100 publications
(99 citation statements)
references
References 33 publications
10
87
2
Order By: Relevance
“…In good agreement with our observations, embryonic cells whose nuclei lack A-type lamins have a much higher nuclear pore density (40-50 NPCs/m 2 ) and proliferation activity (Maul et al, 1980). Furthermore, several studies have reported that the absence or downregulation of lamin A/C is correlated with rapid growth or aggressivity in human malignancies including small-cell lung carcinoma (Broers and Ramaekers, 1994), testicular cancer (Machiels et al, 1997), leukemias and lymphomas (Stadelmann et al, 1990) and skin carcinomas (Venables et al, 2001). These reports support the hypothesis that lamin A/C has a negative influence on cell proliferation.…”
Section: Journal Of Cell Science 119 (21)supporting
confidence: 90%
“…In good agreement with our observations, embryonic cells whose nuclei lack A-type lamins have a much higher nuclear pore density (40-50 NPCs/m 2 ) and proliferation activity (Maul et al, 1980). Furthermore, several studies have reported that the absence or downregulation of lamin A/C is correlated with rapid growth or aggressivity in human malignancies including small-cell lung carcinoma (Broers and Ramaekers, 1994), testicular cancer (Machiels et al, 1997), leukemias and lymphomas (Stadelmann et al, 1990) and skin carcinomas (Venables et al, 2001). These reports support the hypothesis that lamin A/C has a negative influence on cell proliferation.…”
Section: Journal Of Cell Science 119 (21)supporting
confidence: 90%
“…Reduced or null expression of lamins A and C in basal cell carcinomas (BCC) was correlated with a rapid growth rate within the tumour, whereas absence of lamin C only was correlated with a slow growth rate within the tumour [189,190]. In contrast, another study has found the presence of significant amounts of lamins A and C in proliferating BCC cells [191].…”
Section: Skin Cancermentioning
confidence: 99%
“…For immunoblotting, proteins separated on 10% gels were electrophoretically transferred to nitrocellulose (0.2 mm; Schleicher and Schuell) in 48 mM Tris-HCl, pH 9.4, 39 mM glycine by using the Mini Transblot system (Bio-Rad). Primary antibodies were used as follows: anti-myogenin, rabbit polyclonal, 1:500, Santa Cruz Biotechnology; Jol4, anti-lamin-A, mouse monoclonal, 1:10 (Dyer et al, 1997); C-20, anti-lamin-B1, goat polyclonal, 1:500, Santa Cruz Biotechnolgy; anti-lamin-C, rabbit polyclonal, 1:500 (Venables et al, 2001); LN43, anti-lamin-B2, mouse monoclonal, 1:10 (Venables et al, 2001); LAP15, anti-LAP2α mouse monoclonal, 1:10 (Dechat et al, 2000); anti-RbS780, 1:1000, Cell Signalling. Secondary antibodies were donkey anti-mouse, donkey anti-rabbit or donkey anti-goat IgG conjugated to horseradish peroxidase (Jackson Immunoresearch).…”
Section: Cellular Fractionationmentioning
confidence: 99%